Influence of Vacuum Mixing on the Carbonation Resistance and Microstructure of Reactive Powder Concrete Containing Secondary Copper Slag as Supplementary Cementitious Material (SCM). (2017) - Edwin, Romy Suryaningrat; Gruyaert, Elke; Dils, Jeroen; De Belie, Nele
Abstract: This study aims to examine the effect of vacuum mixing on the carbonation resistance and microstructure of reactive powder concrete (RPC), made with secondary copper slag as partial cement replacement. In order to obtain a homogenous mixture, a high speed mixer with vacuum was applied. Accelerated carbonation tests (10% CO2, 20 °C and 60% RH) were performed on RPC, mixed under vacuum conditions, as a comparison to RPC mixed at atmospheric pressure. The evolution of the carbonation depth was determined by spraying phenolphthalein on a freshly split RPC surface at varying ages (1 to 16 weeks). The microstructure of RPC was investigated by a mercury intrusion porosimeter (MIP). The pozzolanic activity of QCS was determined by the Chapelle test, taking into account the carbonation effect on the reference system. The results obtained, showed that no carbonation was detected after 90 days for the RPC containing copper slag both under vacuum condition and atmospheric pressure. The presence of copper slag in the RPC tends to increase the porosity reduction and decrease the strength enhancement when applying vacuum mixing to the mixture. The result of the Chapelle test indicated that the secondary copper slag did not tend to consume much portlandite.